A review of the genus Phalgea Cameron (Hymenoptera: Ichneumonidae: Acaenitinae) with description of a new species from Vietnam - Pham, Nhi Thi; Achterberg, Cees Van (Zootaxa, 2015)
In this paper, the genus Phalgea is reviewed. A new species, Phalgea maculata sp. nov., is described and illustrated from Vietnam. In addition, P. melaptera Wang 1989 is recorded as new for the country. It is the first time the subfamily Acaenitinae is reported from Vietnam.